Lessons in learning. (17th December 2014) - Kemp, Emma; Chambers, Ian
<x xml:space="preserve">Abstract</x> Engaging school children with cutting‐edge science remains challenging. Here, the authors reflect on their experience of developing lessons for high school children about the scientific, medical and ethical implications of stem cell research. <boxed-text content-type="graphic" id="embr201439398-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>